Creep feeding and phytohemagglutinin skin-test responses in pigs - Frank Blecha; D S Pollmann; D M VanWormer (Kansas Agricultural Experiment Station Research Reports, 1984)
An experiment was conducted to determine the influence of creep feeding on cellular immunity in young pigs. Creep feeding from 10 days of age to weaning did not influence phytohemagglutinin skin-test responses.; Swine Day, Manhattan, KS, November 15, 1984
Keywords: Swine day; 1984; Kansas Agricultural Experiment Station contribution; no. 85-132-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 461; Swine; Creep feeding; Phytohemagglutinin skin-test